MISINFORMATION RELATED TO COVID-19 IN INDONESIA - Narila Mutia Nasir; Baequni Baequni; Mochamad Iqbal Nurmansyah (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2020)
Background: An increase in COVID-19 cases has been accompanied by an increase in public misinformation of basic coronavirus facts, its transmission and prevention.Aims: This study described public knowledge of COVID-19 misinformation in Indonesia.Methods: This study was a cross-sectional study using online questionnaires for data collection from 4 to 11 April 2020. The questionnaires consisted of two parts regarding demographic characteristics and knowledge of misinformation. The sample in this study was  530 respondents. Descriptive analysis was used for data analysis.Results: The majority of respondents were below 25 years old (n = 342, 64.5%) and graduated from junior/senior high school education (n = 277, 52.3%). There were 13.2% of respondents who believed the COVID-19 can halt in Indonesia's climate, while 27.7% of them stated that COVID-19 is a biological weapon deliberaly created by a country. Meanwhile, 19.6% believed that gargling with salt water or vinegar can kill the COVID-19.Conclusion: A group of people still did not get misinformation of the COVID-19. Various efforts need to undertake to align community understanding of COVID-19 prevention, and thus they could get accurate  information. Keywords: COVID-19, misinformation, prevention measures, SARC-CoV-2.